Dampak Kehadiran Transportasi Online Terhadap Pendapatan Pengemudi Taksi Kota Konvensional Di Kota Palangka Raya : (Studi Kasus Terminal Mihing Manasa) - Arynovebryana Br. Manihuruk; Alexandro, Rinto; Sundari, Sundari; Kuwing Baboe; Uda, Tonich (Edunomics Journal, 2022)
Revenue is the amount of input obtained for the services provided by the company which may include the sale of products and or services to customers obtained in an operating activity of a company to increase the value of assets and reduce liabilities arising in the delivery of goods or services. The purpose of this study is to find out and describe how the impact of the presence of online transportation on the income of conventional city taxi drivers in Palangka Raya City. The method used in this research is a qualitative method with descriptive analysis method, namely the researcher is intended to collect data or information about an existing phenomenon. The types of data used are primary data and secondary data. Data collection techniques consisting of observation, interviews and documentation. Data analysis was used using techniques from three stages of activities carried out sequentially, namely reducing data, presenting data, and drawing conclusions. The results of the study indicate that the presence of online transportation in Palangka Raya City has an impact on the income of conventional city taxi drivers, namely a decrease in the income of conventional taxi drivers caused by fare problems, convenience, security and the shift of passenger interest. The existence of online transportation services in the City of Palangka Raya has an impact on city taxi drivers (angkot), which causes them to experience a reduction in passenger interest.